Workforce utilization of Canadian men with a nursing education - Christoph Schimmele; Feng Hou (Economic and Social Reports)
Little is known about the workforce utilization of Canadian men with a nursing education, who accounted for 12% of people eligible to practise nursing in 2021 (Canadian Institute for Health Information, 2022).